The haemodynamic demand and the attributes related to the displacement of the soccer referees in the moments of decision / intervention during the matches. (3rd March 2020) - Lima e Silva, L.; Neves, E.; Silva, J.; Alonso, L.; Vale, R.; Nunes, R.
ABSTRACT: The present study aimed to analyze the hemodynamic variables and the displacement variables, the former being heart rate (meanHR), maximum heart rate (maxHR) and minimum heart rate (HRmin), and the latter being average speed (Vmed), maximum speed (Vmax), mean cadence and distance traveled during referee interventions in matches of the Brazilian national football league. 1224 observable decisions of 10 professional soccer referees from Rio de Janeiro were analyzed. Three moments were considered: the moment of decision (D0), the 15 seconds that preceded it (D15), and the period from the beginning of each step to the decision (DA). It was observed a high hemodynamic load in the moments analyzed. The meanHR in the 10 matches was 160.5±8.33, the results showed very high maxHR values, the highest value found was 222bpm. Regarding the comparison between the halves of the game: 1st half (1st) and 2nd half (2nd), the initial stage of the matches, requires more intense displacements with lower hemodynamic pressure. The results suggest that cognitive decision making influences hemodynamic variables. Apparently, in the second stage of the matches, due to the accumulation of exercise demanded in the previous stage, the referees adopted a condition of saving of energy.